Perspektif ASEAN Terhadap Prinsip Non-Intervensi - Arum Widiastuti (Jurnal USM Law Review)
This study aims to examine the implementation of the Non-Intervention Principle for ASEAN member countries. This study uses a normative juridical research method. ASEAN was founded under the Bangkok Declaration on August 8, 1967, with ten members from Southeast Asia still adhering to the principle of Non-Intervention enshrined in the 1976 Treaty of Friendship and Cooperation in Southeast Asia (TAC) and the ASEAN Charter. ASEAN has grown into a large international organization and is starting to be respected by the international community, the principle of Non-Intervention is still a persistent problem in ASEAN, and ASEAN leaders must think about flexibility. This principle is intended to assist a Member State in dealing with problems, particularly those concerning humanity. The results of this study explain that the principle of Non-Intervention that has been maintained so far has greatly contributed to the existence of ASEAN. The application of the principle of Non-Intervention should not be done rigidly so that law enforcement agencies in the field of human rights have a margin of maneuver to formulate recommendations or contributions about what should be a member state.